Entrepreneurship education and established business activities: An international perspective - He, Liangxing; Zheng, Leven J; Sharma, Piyush; Leung, Tak Yan (Elsevier, 2023)
This paper introduces a conceptual model with perceived opportunity and perceived capability as mediators in the process by which entrepreneurship education helps improve the established business activities. Specifically, we hypothesize that the prevalence of entrepreneurship education relates positively with the rate of established business activity, and that perceived opportunity and capability mediate this relationship. We find support for all our hypotheses using Poisson regression with the Global Entrepreneurship Monitor data collected from 826 participants across 107 countries during the 2001–2018 period. Our findings confirm that entrepreneurship education has a significant positive impact on the performance of established businesses by helping the entrepreneurs improve their perceived capabilities and opportunities. These findings extend the current research on the impact of entrepreneurship education on entrepreneurial activities at different stages of development for entrepreneurial businesses.